Effects of automotive diesel oil on germination of Avicennia germinans and Laguncularia racemosa mangrove propagules - Josélia Castro da Silva MARTINS; Flávia Rebelo MOCHEL; Ilisandra ZANANDREA; James Werllen de Jesus AZEVEDO; Leonardo Gonçalves de LIMA; Denilson da Silva BEZERRA; Emilly Gabrielle do Nascimento ABREU; Marcelle da Silva e SILVA; Aline Maria Silva LIMA (Acta Amazonica, 2023)
ABSTRACT Mangrove ecosystems are sensitive to oil, as spills can impair developmental processes of mangrove vegetation. Since the 2010s, the Brazilian equatorial margin, more specifically the Pará-Maranhão Basin and the mouth of the Amazonas River, has been affected by oil runoff from urban activities and the increased risk from exploratory deepwater drilling for oil extraction. Dispersal of mangrove propagules occurs during the tidal cycles, when the presence of tensors in the water can affect germination. We analyzed the effects of diesel oil on the germination of propagules of the two most common mangrove species in the region, Laguncularia racemosa and Avicennia germinans, in six treatments of diesel oil in the water (0.5%, 1%, 1.5%, 2%, 3% and 4%) and a diesel-free control. The response variables were germinability (G%), mean germination time, mean germination speed and the germination speed index (GSI). G% and GSI in L. racemosa propagules differed significantly between the control and all treatments (G% and GSI < 10% in the 3% treatment). Propagules of A. germinans were more resistant, and the physiological variables did not differ significantly among treatments and control (G% > 90% in all treatments). Our results indicate that, at the germination stage, L. racemosa was more susceptible than A. germinans to contamination by automotive diesel oil.